Ethosomes in Nanomedicine: A Comprehensive Review of Formulation Strategies and Therapeutic Applications - Tulsi G. Patel; Saloni B. Gohil; Sanskruti M. Rao; Pankti N. Patel; Bhavin D. Pandya; Kautuk P. Shah; Ajay K. Saluja; Shreyash A. Diwakar (Asian Journal of Pharmaceutical Research and Development, 2026)
Ethosomes are novel lipid vesicular carriers that enhance drug delivery through the skin. Due to their high ethanol content, they offer improved flexibility and permeability, enabling drugs with diverse physicochemical properties to reach both superficial and deep skin layers.Introduced in 1996, ethosomes have been extensively investigated and modified, resulting in the development of new generations with optimized compositions. These systems can be incorporated into formulations such as gels, patches, and lotions, and are prepared using several innovative methods.Both preclinical studies and clinical trials confirm the efficiency of ethosomes in dermal and transdermal drug delivery. Compared with conventional liposomes, ethosomes demonstrate superior skin penetration and therapeutic effectiveness, making them a promising platform for future pharmaceutical applications.